Uganda climate smart-agriculture country program 2015-2025 - Ministry of Agriculture, Animal Industry and Fisheries, Uganda; Ministry of Water and Environment, Uganda (2015)
The agriculture sector is a key to overall economic growth and development of Uganda. The sector contributes 20.9 percent of the National Gross Domestic Product and 80 percent of the export earnings. Real growth in agricultural output has declined steadily, from 7.9 percent in 2000/01 to 0.7 percent in 2007/08 (although it did show signs of recovery in 2008/09, with a 2.6 percent growth rate). Agricultural production has increased over the years and this increase is attributed to area expansion rather than increase in productivity with over 95% of the farmers being smallholders with landholdings averaging 2 ha.